Saving the Seat of Democracy: The Restoration of the Palace of Westminster. (10th August 2022) - Ellison, Jennifer; Rowley-Conwy, Eleanor; Sims, Aimee
ABSTRACT: The Palace of Westminster is a Grade 1 listed building and a designated UNESCO World Heritage Site that is deteriorating faster than it can be repaired, increasing the risk of sudden and catastrophic failure. In 2018 the Restoration and Renewal (R&R) Programme was established to transform the Houses of Parliament and safeguard their future as the working home of British parliamentary democracy. It is a multifaceted and challenging undertaking, with key considerations for the architectural fabric and parliamentary heritage required to ensure it is fit for purpose in the twenty-first century. This paper will explore the impact conservation has had on planning, risk mitigation and project management by discussing how to raise heritage awareness and the complex approach to governance required due to the nature of the R&R Programme. It will focus on building information modelling, Palace surveys and sustainability considerations as specific case studies of conservation deliverables, whilst also showcasing the utilisation of innovative and cross-disciplinary techniques that have allowed the re-imagining of traditional construction methodologies.